Non-pharmacological treatment methods for irritable bowel syndrome - literature overview - Wojciech Urban; Kornelia Karamus; Rafał Wojciech Rejmak; Jan Biłogras; Martyna Borowska-Łygan; Konrad Strużek; Jakub Tomaszewski (Journal of Education, Health and Sport)
Introduction